Bribery, Plant Size and Size Dependent Distortions - Tamkoç, M. Nazin (World Bank, Washington, DC, 2022)
This paper studies the relationship between distortions, plant size, and bribery possibilities. In a distorted economy, bribery is a transfer from a private party to government officials to ‘get things done’. Enterprise Surveys data shows that small plants spend a higher fraction of their output on bribery than big plants. In this paper, a one-sector growth model is developed in which size-dependent distortions, bribery opportunities, and different plant sizes coexist. In the model, bribery is endogenous in the sense that managers decide to use it as a way to deal with distortions. Two sets of exercises are conducted to quantify the interplay of size-dependent distortions and bribery. First, the model parameters are calibrated to generate the plant size distribution of the U.S., by assuming the U.S. is free of distortions. Then, size-dependent distortions are introduced to the undistorted economy, and their effects with and without bribery opportunities are compared. Counterfactual exercises show that size-dependent distortions become less distortionary in the presence of bribery opportunities since plants are able to avoid distortions by paying larger bribes. Second, the model is calibrated with distortions and bribery opportunities using Turkish data. The choice of this country for analysis does not imply that bribery or size-dependent distortions are particularly large in Türkiye relative to countries of comparable development. The choice is driven by the availability of data on both the plant size distribution and spending on bribery in the country. The results indicate that the inferred level of distortions is sizable for all plants. The removal of distortions, which would eliminate the incentive for paying bribes, can have a substantial effect on both the output and the mean plant size which could increase by 63.6 and 82.5 percent, respectively.